Pemanfaatan Limbah Botol Plastik dan Kaca Menjadi Produk Kreatif - Supiatun Supiatun; Miftahul Jannah; Ela Nindriyani; Neta Dian Lestari (Universitas Tarumanagara, 2021)
The problem of waste is a common problem in the world, in the era of the Industrial Revolution 4.0, ready-to-eat food and beverage products resulted in piles of waste which resulted in environmental pollution. Waste that can damage the environment is waste that cannot be decomposed by nature. As a form of saving the earth to reduce the waste of plastic bottles and glass bottles, the younger generation should be able to use them such as pencil boxes, plastic flower vases, chairs, multipurpose storage places and bross. Meanwhile, waste glass bottles can be made into products such as miniatures, flower pots and home decorations. Permasalahan sampah menjadi masalah bersama didunia, pada era Revolusi Industri 4.0, produk makanan dan minuman kemasan siap saji mengakibatkan timbunan sampah yang mengakibatkan pencemaran lingkungan. Sampah yang dapat merusak lingkungan adalah sampah yang tidak dapat terurai oleh alam. Sebagai bentuk penyelamatan bumi mengurangi limbah botol plastik dan botol kaca, sebagai generasi muda harus dapat memanfaatkan seperti kotak pensil, vas bunga bunga dari plastik, kursi, tempat penyimpanan serbaga guna dan bross. Sedangkan limbah botol kaca dapat dibuat produk seperti miniatur, pot bunga dan hiasan rumah.